The impact of garlic use on human health. A review of its therapeutic potential and application in athletes - Borawski, Michał; Ciuła, Aleksandra; Jakubiak, Anna; Miśkiewicz, Joanna; Mularczyk, Klaudia; Karaban, Łukasz; Kupis, Magdalena; Kuźnieców, Tadeusz; Znamirowska, Patrycja; Paszkowska, Monika (Quality in Sport, 2025)
The abundance of bioactive compounds present in garlic positions it as a promising agent in the support of human health. This paper constitutes a review of scientific literature published over the past five years, with sources identified through a search of the PubMed database. The review explores the effects of garlic on hypertension, lipid metabolism, atherosclerosis, retinopathy, physical performance, organ perfusion, and the risk of developing certain malignancies — particularly gastric and prostate cancers. Current research indicates that regular garlic consumption may contribute to the reduction of blood pressure, improvement of lipid profiles, and attenuation of oxidative stress and inflammatory markers. Furthermore, it may decrease the risk of vascular complications and the incidence of selected cancers. Evidence also suggests a beneficial impact on cerebral perfusion and a reduction in symptoms of erectile dysfunction. Nonetheless, further clinical trials employing rigorous methodologies are required to definitively establish its efficacy.